2017
DOI: 10.1200/jop.2016.015396
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely: Opportunities for Improving Value in Cancer Care Delivery?

Abstract: QUESTION ASKED: What is the concordance with ASCO and the American Society for Therapeutic Radiology and Oncology Choosing Wisely (CW) measures and the cost associated with nonconcordance?SUMMARY ANSWER: Baseline concordance with selected CW measures ranged from 39% to 94%, with marked variability by cancer center. Nonconcordance was associated with higher total Medicare costs for every measure. WHAT WE DID:We conducted a retrospective analysis of Medicare claims data from 2012 to 2015 to examine concordance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…One possibility is the Choosing Wisely campaign itself and the associated media coverage, although rates of testing in Michigan appeared to start decreasing before the publication. 9,13,20 Those sites with the highest percentage of nonconcordant testing of patients with stage II disease treated fewer patients compared with those with lower rates of testing, although numerous other sites that treated smaller numbers of patients also had low rates of testing. 11 Furthermore, numerous studies have demonstrated a significant lag in the uptake of new guidelines or findings by physicians following their initial publication or presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is the Choosing Wisely campaign itself and the associated media coverage, although rates of testing in Michigan appeared to start decreasing before the publication. 9,13,20 Those sites with the highest percentage of nonconcordant testing of patients with stage II disease treated fewer patients compared with those with lower rates of testing, although numerous other sites that treated smaller numbers of patients also had low rates of testing. 11 Furthermore, numerous studies have demonstrated a significant lag in the uptake of new guidelines or findings by physicians following their initial publication or presentation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support and extend those reported in the literature. [9][10][11][12][13] The Choosing Wisely recommendations were developed to reduce the use of advanced imaging in asymptomatic patients with newly diagnosed stage 0-II breast cancer because of the minimal benefits and potential harms of testing. The likelihood of having metastatic disease in this setting has been demonstrated to be less than 2% in multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing Wisely is another attempt to bring attention to the problem of waste in health care testing and treatment; the American Board of Internal Medicine launched the Choosing Wisely Campaign in 2012 . Leading medical specialty societies were asked to identify tests, procedures, and treatments that are commonly used and often unnecessary.…”
Section: Delivery Of Cancer Control Services In the United Statesmentioning
confidence: 99%
“…Choosing Wisely is another attempt to bring attention to the problem of waste in health care testing and treatment; the American Board of Internal Medicine launched the Choosing Wisely Campaign in 2012. 29 Leading medical specialty societies were asked to identify tests, procedures, and treatments that are commonly used and often unnecessary. The American Academy of Family Physicians suggested limiting some practices related to cervical, prostate, and testicular cancer screening, and some recommendations vary by professional society.…”
Section: Assessment and Preventionmentioning
confidence: 99%
“…Despite marked differences in resources, cultures, and environments, hospital systems in countries of all income levels continuously work to improve the quality of patient care . New perioperative pathway development requires thoughtful planning and careful implementation to limit unforeseen negative consequences, maximize positive impacts, and promote patient‐centeredness .…”
mentioning
confidence: 99%